DETERMINATION OF THE HEAT RESISTANCE OF NEW WHEAT SEEDS IN LABORATORY CONDITIONS - R. Isabekov (Galaxy International Interdisciplinary Research Journal, 2023)
The heat resistance of new wheat cultivar seeds was studied under laboratory conditions. As a result of the experiment, it was found that wheat seed named ODARI has medium resistance to heat, and all wheat varieties shown in the table have high resistance from 85% to 98%.